(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
The present investigations’ aim is to analyze works that present garments and light embroidered textiles in order to observe which are the main uses in theatrical spaces or for which other means light (in this case, set up on the body) could be applied. The study is part of an investigation for the art direction of Hamlet-Machine (Heiner Muller; 2017) spectacle organized by Teatro Ludos, AdaLab and LATA, all projects from the Federal University of Goiás (Brazil). Eight virtual meetings during the quarantine period (COVID- 19) were organized in order to discuss about Hamlet (Shakespeare) and Hamlet-Machine (Heiner Muller) texts but also to debate about the history of fashion, identities, as well as theater masks. During the discussions we decided to adopt topics like trans-humanism and the non-viability in detaching from the complex systematization of digital exchanges in our daily life. We are interested in using lightened garments and objects that can easily fit with the body mobility. While we can not have presential meetings to develop the ideas further, during COVID-19 pandemics quarantine we can previously investigate the relationship between lightening and garments. With a few results we observed that light and garments are usually presented in theatrical or performative forms as a special effect (effect justified according to Cibele Forjaz Simões, 2015 sayings) or in a similar way that black theater light is used to work. We also found more recent works in which the light use is part of the method or the internal procedures used by the artist, dancer or performer. We realized that there are still places for a more “pervasive” light, that can make the actors or the space around them visible, but also, an embroidered light in garments that can contribute to the spectacle’s visuality.